Examining the measurement invariance of the teachers' sense of self-efficacy scale in terms of gender - Yıldız Burcu Doğan; Huseyin Akar; Mehmet Üstüner (International Journal of Evaluation and Research in Education (IJERE), 2019)
The aim of this research was to analyze the measurement invariance of the "Teachers' Sense of Self-Efficacy Scale," developed by Tschannen-Moran and Hoy, and adapted into Turkish and Turkish culture by Çapa, Çakıroğlu and Sarıkaya, with respect to gender. Turkish version of the scale consists of 24 items and 3 subscales. The scale measures pre-service teachers' and teachers' sense of and belief in self-efficacy for student engagement, classroom management and instructional strategies. Research revealed that the scale is being used by a myriad of researchers. The sample of this study consists of 267 female, 163 male pre-service teachers who participated in the Pedagogical Formation Certificate Traning at Inönü University in the 2017-2018 academic years. First of all, CFA was executed in order to confirm the validity of the scale's current structure for both genders which was confirmed based on the analysis results. Then, MGCFA was executed to analyze the scale's measurement invariance in terms of gender. The results of the MGCFA indicated that the scale has the measurement invariance with respect to gender at each of the stages of strict, metric, scalar and configural invariance.